ANALISIS KINERJA PELAYANAN PENDIDIKAN (Studi Pada Dinas Pendidikan Dan Kebudayan Kota Serang) - Lies Tyedono; Ridho Ridho (http://jurnal.untirta.ac.id/index.php/JIPAGS, 2018)
The studi aims to find out the basic service performance at the Department of Education and Culture in Serang City. The research lays on questing the influencing factors with respect to the basic service performance at the Department. A hundred questioners was answered by teachers living in the city, coming along with semi-structured interviews. Respondents were selected based on their experiences in accessing government educational service. This research has indicated adequate performance of the Department’s officers seen from adequate numbers of personnells, proper skills, suitable knowledge. Nonetheless, suppoting resources and personnels behaviours seem to have been inadequate. Slow service respons were indicated as the first issue, followed by lack of suitable and up-to-date public service skills. This study suggests the needs to have a system analysis along with the analysis of required resources in terms of adequate realocation of the resources. As well, it is a necessity to design mechanism in which people can send their complains regarding the service. Personnels analysis is needed to have a sense of identification in determining human resources issues. Overall, the research recommends leadership measures as to be included in assessing service performance.